Normalization of glomerular filtration rate in obese children - Correia-Costa, Liane; Schaefer, Franz; Afonso, Alberto Caldas; Bustorff, Manuela; Guimarães, João Tiago; Guerra, António; Barros, Henrique; Azevedo, Ana (Pediatric nephrology, 2016)
Glomerular filtration rate (GFR) is conventionally indexed to body surface area (BSA), but this may lead to biased results when applied to subjects of abnormal body size. The aim of our study was to examine the impact of normalization to the BSA and alternative body size descriptors on measured and estimated GFR in overweight and obese children.